2015
DOI: 10.1007/s00380-015-0708-7
|View full text |Cite
|
Sign up to set email alerts
|

Aortic smooth muscle cell alterations in mice systemically exposed to arsenic

Abstract: Previous epidemiological studies showed that chronic arsenic exposure is related to increased cardiovascular disease incidence. The detailed biochemical mechanisms by which arsenic exerts its effects remain unknown. Vascular disease progression is characterized by smooth muscle cell (SMC) phenotypic switching, vessel wall reorganization, and platelet-derived growth factor (PDGF) production. The objective of this study was to examine early biochemical and structural changes in the aortas of ICR mice systemicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Previous studies indicated that both the mean systolic and diastolic arterial pressures and body weights in mice fed a high arsenic dose (20 mg/kg) were not significantly different from those in control mice 6 , 10 . Our results showed that mice systemically exposed to various doses of arsenic were not significantly different from control mice in terms of growth and behavior, suggesting that arsenic doses of 10-20 mg/kg body weight do not produce any undesirable physiological stress or overt toxicity in ICR mice.…”
Section: Discussionmentioning
confidence: 85%
“…Previous studies indicated that both the mean systolic and diastolic arterial pressures and body weights in mice fed a high arsenic dose (20 mg/kg) were not significantly different from those in control mice 6 , 10 . Our results showed that mice systemically exposed to various doses of arsenic were not significantly different from control mice in terms of growth and behavior, suggesting that arsenic doses of 10-20 mg/kg body weight do not produce any undesirable physiological stress or overt toxicity in ICR mice.…”
Section: Discussionmentioning
confidence: 85%
“…Arsenic exposure is associated with a wide range of cardiovascular disorders including coronary heart disease, hypertension, aortic diseases, and increased risk of cardiovascular mortality (Chen, 2016;Farzan, 2015;Gunduz, 2015;Islam, 2012;James, 2015). Cardiovascular effects of arsenic exposure are not limited to these disorders, but also have a significant influence on cardiac conduction system (Alamolhodaei, 2015;Stea, 2014).…”
Section: Introductionmentioning
confidence: 99%